Effectiveness of the Photofenton Process in Treating Wastewater from the IPLT Oxidation Ditch Outlet - Nur Oktavia Nikmatin Hasanah; Mohamad Mirwan; Rizka Novembrianto (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Wastewater from the Sludge Treatment Plant (IPLT) often contains hazardous contaminants that can pollute water bodies if discharged without prior treatment. Wastewater treatment from the IPLT, especially the Oxidation Ditch outlet, can be carried out using one of the Advanced Oxidation Processes (AOPs), namely Fenton. This study aims to analyze the effectiveness of the Fotofenton method in the Oxidation Ditch outlet unit of the Keputih IPLT, Surabaya, on total coliform, COD, and TSS parameters. The total coliform removal percentage was 98%, the COD parameters were 82%, and the TSS parameters were 60% at a dose of FeSO4: H2O2 molar ratio of 1:15, UV lamp power of 20 watts, and sampling time of 60 minutes. This study demonstrates that the Fotofenton method can be an environmentally friendly solution for wastewater treatment from IPLT and can be applied as an advanced treatment stage to meet applicable quality standards. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 3: Good Health and Well-BeingSDG 12: Responsible Consumption and ProductionSDG 14: Life Below Water